Understanding Innu normativity in matters of customary “adoption” and custody - Grammond, Sébastien; Guay, Christiane (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2017)
This article presents the preliminary results of a research project on customary custody and “adoption” in the Innu community of Uashat mak Mani-Utenam in northeastern Québec. From a legal pluralist perspective, the authors used a biographical method to understand the workings of the ne kupaniem/ne kupanishkuem Innu legal institution, which can be compared in certain respects to adoption in Western legal systems. The authors present certain characteristics of this institution in order to expose the limits of bills that seek to recognize “indigenous customary adoption” in Québec law. Innu “adoption” stems from an agreement between the concerned persons, which can crystallize gradually, which never breaks the original filial link, and which does not immediately create a new filial link. In theory, this type of adoption is not permanent. As such, a Québec law that only recognizes indigenous adoptions that create a new filial link runs the risk of either being ineffective, or of distorting the Innu legal order.